Age-related analysis of the gut microbiome in a purebred dog colony. Issue 8 (2nd May 2019) - Mizukami, Keijiro; Uchiyama, Jumpei; Igarashi, Hirotaka; Murakami, Hironobu; Osumi, Takafumi; Shima, Ayaka; Ishiahra, Genki; Nasukawa, Tadahiro; Une, Yumi; Sakaguchi, Masahiro
ABSTRACT: Dogs are model animals that can be used to study the gut microbiome. Although the gut microbiome is assumed to be closely related to aging, information pertaining to this relationship in dogs is limited. Here, we examined the association between the canine gut microbiome and age via a bacterial 16S rRNA gene amplicon sequence analysis in a colony of 43 Japanese purebred Shiba Inu dogs. We found that microbial diversity tended to decrease with aging. A differential abundance analysis showed an association of a single specific microbe with aging. The age-related coabundance network analysis showed that two microbial network modules were positively and negatively associated with aging, respectively. These results suggest that the dog gut microbiome is likely to vary with aging. Abstract : Gut microbiome analysis in a Shiba Inu purebred dog colony shows age-related transition of not only microbial diversity, a specific microbe, but also modules of a microbial coabundance network.